(untitled) (Desenvolvimento em Questão, 2026)
The growing demand for transparency has consolidated sustainability reports and Environmental, Social, and Governance (ESG) practices as fundamental elements of organizational strategies. This study aims to analyze how international scientific literature has addressed the relationship between the disclosure of ESG practices and sustainability reporting from 2008 to 2025. The methodological approach consisted of a bibliometric analysis guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol, based on scientific performance indicators, co-authorship networks, and keyword co-occurrence. The results reveal an exponential growth in publications after 2019 and a shift from theoretical approaches to more pragmatic perspectives, with an emphasis on governance and climate risk management. The thematic evolution indicates an increasing sophistication of research, moving from broad notions such as social responsibility to more strategic themes, including the governance approach, climate risk, and industrial performance. It is concluded that the literature has advanced in understanding the integration between sustainability reporting and ESG practices. Future studies are encouraged to explore the use of emerging technologies, such as artificial intelligence, in the analysis of sustainability data.